PENGELOLAAN DANA ZAKAT DALAM BENTUK PENDISTRIBUSIAN SAPI OLEH PESANTREN TALAGO DADOK BERDASARKAN UU PENGELOLAAN ZAKAT - Ashabul Fadhli; Desy Farina; Iljas Madi; Juarsa Badri (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
It is known that Talago Dadok Islamic Boarding School become one of the mustahik who receive zakat in  conventional productive form by BAZNAS Solok Regency. The zakat received by Talago Dadok Islamic Boarding School in the form of the purchase of 8 (eight) cows as business capital. The proceeds from the effort will be used to pay the salaries of ustadz and ustadzah who teach at Talago Dadok Islamic Boarding School because they do not have a fixed income. Based on the findings and information provided by the implementing officer baznas Solok Regency, the author found some problems appear in the future after the cows raising runs for several months.Through the report provided by Talago Dadok Islamic Boarding School to Province, the relevant office and BAZNAS Solok Regency, there are very significant weaknesses in the aspects of financial statements and bookkeeping. This research is conducted as a field research using sociological approach. This research is interesting to be studied considering that Talago Dadok Islamic Boarsing School has no history of expertise in the field of cow rearing. The findings resulting from this study are that there are many aspects that must be improved by Talago Dadok Islamic Boarding School, especially in the administrative aspect.